Circulars of administrative reforms in the civil service of Malaysia ( 1991-1996) - Malaysia.Government of Malaysia (Kuala Lumpur, 1995)
This book contains circulars of administrative reforms in the civil service of Malaysia ( 1991-1996)
Keywords: Civil services-Malaysia